Cumulative Effect of Medical and Social Risk Factors on Routine Prenatal Care Screening [A231]. (May 2022) - Pennathur, Harini; Ghrayeb, Leena; Debnath, Dipra; Ganzi, Stephanie; Cohn, Amy; Peahl, Alex F.
Abstract : INTRODUCTION: Social risk factors affect prenatal care attendance; however, little is known about how cumulative medical and social risk factors influence receipt of prenatal services. We describe the association between medical and social risk factors and the timing of a routine prenatal care screening: gestational diabetes (GDM). METHODS: We identified patients with a GDM diagnosis receiving prenatal care at a single institution from January 1 to December 31, 2018. We divided patients into four groups by medical and social risk factors in the electronic health record: completely low-risk, social risk only, medical risk only, and completely high-risk. We compared the timing of GDM diagnosis and time for all group members to receive the GDM diagnosis. The study was deemed exempt by the institutional review board. RESULTS: We identified 102 patients with GDM: 11 (10.8%) completely low-risk, 17 (16.7%) social risk only, 11 (10.8%) medical risk only, and 63 (61.8%) completely high-risk. The median gestational age of diagnosis for GDM was 28.6 weeks (IQR, 27.2–30.9) and was similar across groups: completely low-risk 28.8 (IQR, 27.4–30.9) weeks, social risk only 28.2 (IQR, 27.1–29.6) weeks, medical risk only 29.2 (IQR, 27.6–30.1) weeks, and completely high-risk 28.6 (IQR, 26.9–31.4) weeks. The time for all patients to be diagnosed was later for groups with social risk factors, regardless of medical risk factors: completely low-risk 32 weeks, social risk only 35 weeks, medical risk only 30 weeks, and completely high-risk 36 weeks. CONCLUSION: Many patients with social risk factors were diagnosed with GDM later in pregnancy. Attention to social risk factors can potentially improve timeliness of diagnosis of pregnancy complications and pregnancy outcomes.